2019
DOI: 10.1186/s12909-019-1568-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported motivation for choosing nursing studies: a self-determination theory perspective

Abstract: Background The nursing shortage is of worldwide concern, with nursing student retention acknowledged as a priority. As a fundamental step towards exploring factors that can guide the implementation of strategic approaches to retain undergraduate nursing students and prevent their attrition, the aim of this study is to examine the motivation for choosing nursing studies of first-year nursing students within the theoretical framework of self-determination theory. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
0
45
0
2
Order By: Relevance
“…Such research has found that these choices are the result of a combination of internal and external motivational factors; sometimes, nursing is not students’ first options. Students choose to engage in the nursing profession based on their desire to help other people and engage in activities and perform work with social benefits [ 24 27 ]. External motivational factors, such as career opportunities and job security, are also important in students’ career choices [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such research has found that these choices are the result of a combination of internal and external motivational factors; sometimes, nursing is not students’ first options. Students choose to engage in the nursing profession based on their desire to help other people and engage in activities and perform work with social benefits [ 24 27 ]. External motivational factors, such as career opportunities and job security, are also important in students’ career choices [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students choose to engage in the nursing profession based on their desire to help other people and engage in activities and perform work with social benefits [ 24 27 ]. External motivational factors, such as career opportunities and job security, are also important in students’ career choices [ 24 , 26 , 27 ]. Personal health-related experiences such as hospitalisation, the illness of a family member, or a volunteering experience, have been detected as additional motivations [ 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The external extreme of the motivational scale seems occupied by motivation related to the topic of study and search of job opportunities. A large proportion of students (74%) indicated altruistic motivations for choosing nursing studies, corresponding to the literature on this topic [39,40,41,42,43,44,45]. The analysis of gender differences shows that the internal motivations are more present in females' responses to the open question, as opposed to male responses, more oriented towards external motivations.…”
Section: Discussionmentioning
confidence: 73%
“…This choice is a result of a combination of internal and external motivational factors and, sometimes, it is not the rst option. Students choose the nursing profession based on their desire to help other people and engage in activities and perform a work with a social bene t [39,40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…As there is a nurse shortage worldwide, it is important that students chose to study nursing and are highly motivated during the study [3]. As defined by Rafii et al [4], the academic motivation of nursing students is "a broad and multidimensional concept that is affected by various personal, family, social, educational, and professional factors".…”
Section: Introductionmentioning
confidence: 99%